Exploring early purchasing involvement in discontinuous innovation: A dynamic capability perspective. Issue 4 (October 2019) - Picaud-Bello, Katia; Johnsen, Thomas; Calvi, Richard; Giannakis, Mihalis
Abstract: This paper aims to address the gap concerning our knowledge about early purchasing's involvement (EPI) in new product development (NPD) projects in contexts characterized by discontinuous innovation. We adopt a dynamic capability perspective to explore how existing sourcing and supplier relationship management capabilities are adapted when purchasing agents become involved in discontinuous innovations projects. We use an embedded case-study approach to study four NPD projects in a heating, ventilation, and air conditioning (HVAC) company. The case studies are based on interviews with managers and staff from the research and development, purchasing, and marketing departments, as well as suppliers involved in the projects. Our empirical findings capture emerging purchasing practices including a "reversed" sourcing process, purchasing-marketing interaction, and the coordination of "a learning atmosphere" between the R&D department and suppliers through proactive innovation meetings and creativity workshops. We derive propositions to conduct further research into the role of the purchasing department in times of discontinuous innovation. We also provide a framework of sourcing and supplier-relationship practices that firms can use when embarking on discontinuous innovation. Highlights: A dynamic capability approach is adopted to explore purchasing involvement in discontinuous innovation. Two propositions are developed to guide future research into the role of the purchasing department early in the NPD process for discontinuous innovation. A managerial framework of detailed sourcing and supplier-relationship practices used for discontinuous innovations is proposed. The proposed managerial framework can be used to guide the implementation of new sourcing and supplier relationship management capabilities for discontinuous innovation.